2016
DOI: 10.1159/000445883
|View full text |Cite
|
Sign up to set email alerts
|

Creative Music Therapy in an Acute Care Setting for Older Patients with Delirium and Dementia

Abstract: Background/Aims: The acute hospital ward can be unfamiliar and stressful for older patients with impaired cognition, rendering them prone to agitation and resistive to care. Extant literature shows that music therapy can enhance engagement and mood, thereby ameliorating agitated behaviours. This pilot study evaluates the impact of a creative music therapy (CMT) programme on mood and engagement in older patients with delirium and/or dementia (PtDD) in an acute care setting. We hypothesize that CMT improves enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 31 publications
1
105
0
1
Order By: Relevance
“…All interventions were delivered on the ward, other than one study where the training was delivered online for staff to access at home . The majority (13/24, 54%) of studies evaluated multicomponent staff educational interventions aiming to improve dementia care on the ward (medical model of dementia, approaches to communication and behaviour, dementia‐friendly care, connecting with the carer, communicating with patients, dementia‐related behaviour, wandering and falls, managing BPSD, nutrition and hydration, importance of activities, falls management, and end‐of‐life care), followed by person‐centred care (3/24), specialist geriatric medical ward, improving communication and relationship (using experiential learning therapy with actors trained to portray patients living with dementia) between staff and family carers, and creative music therapy . One technology‐based intervention was a humanoid robot for psychomotor therapy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All interventions were delivered on the ward, other than one study where the training was delivered online for staff to access at home . The majority (13/24, 54%) of studies evaluated multicomponent staff educational interventions aiming to improve dementia care on the ward (medical model of dementia, approaches to communication and behaviour, dementia‐friendly care, connecting with the carer, communicating with patients, dementia‐related behaviour, wandering and falls, managing BPSD, nutrition and hydration, importance of activities, falls management, and end‐of‐life care), followed by person‐centred care (3/24), specialist geriatric medical ward, improving communication and relationship (using experiential learning therapy with actors trained to portray patients living with dementia) between staff and family carers, and creative music therapy . One technology‐based intervention was a humanoid robot for psychomotor therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Music therapy: One before‐and‐after study evaluated this therapy. It reported a statistically significant difference in levels of pleasure and alertness (The Lawton Observed Emotion Rating Scale; OERS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, therapy is used to reduce anxiety and promote relaxation among these patients. The impacts of musical therapy were further demonstrated in a systematic review by Abraha et al [28] although further studies are required to ascertain this literature.…”
Section: Music Therapy In Managing Deliriummentioning
confidence: 94%
“…Non-pharmacological interventions for managing Delirium are dependent on patient factors and the healthcare providers' selection. In the systematic review by Abraha et al [28] in using the non-pharmacological management for patients above 60 years, it was revealed that multicomponent approach is essential in preventing the condition and that the interventions are profound when administered to the patient at high risk of developing the condition. This review further revealed that for the single component management approaches, only the reorientation protocol, staff education, and Geriatric Risk Assessment Med Guide had significant outcomes in reducing the condition severity.…”
Section: Comparing Different Non-pharmacological Approachesmentioning
confidence: 99%